2018
DOI: 10.14238/pi58.4.2018.170-4
|View full text |Cite
|
Sign up to set email alerts
|

Lung function in athletes and non-athletes aged 13-15 years

Abstract: Background Regular sports or physical training contributes in increasing the body’s pulmonary function. The increase of pulmonary function is determined by the strength of respiratory muscle, thoracic compliance, upper respiratory system resistance, and pulmonary elasticity. Objective To compare pulmonary function between athletes and non-athletes aged 13-15 years. Methods This is a cross-sectional analytical study conducted onnior high school students aged 13-15 years throughout June to August 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…On the other hand, there was no significant difference in FEV1/FVC volume capacities. Vignesh et al (2018) stated that the FEV1 volume capacity of individuals who exercise regularly is higher than that of individuals who do not, and regular exercises have a great effect on lung function, while Saputri et al (2018) reported that the FEV1/FVC ratio will be better in individuals who do sports (13-15 years) than those who do not exercise. Minaeifar et al (2020) maintained that the FEV1 volume capacities of factory employees who did sports were higher than those who did not in their study carried out with 74 roof tile factory employees.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there was no significant difference in FEV1/FVC volume capacities. Vignesh et al (2018) stated that the FEV1 volume capacity of individuals who exercise regularly is higher than that of individuals who do not, and regular exercises have a great effect on lung function, while Saputri et al (2018) reported that the FEV1/FVC ratio will be better in individuals who do sports (13-15 years) than those who do not exercise. Minaeifar et al (2020) maintained that the FEV1 volume capacities of factory employees who did sports were higher than those who did not in their study carried out with 74 roof tile factory employees.…”
Section: Discussionmentioning
confidence: 99%